CFD modeling of natural ventilation in a void connected to the living units of multi-storey housing for thermal comfort - Muhsin, Fakhriah; Mohammad Yusoff, Wardah Fatimah; Mohamed, Mohd Farid; Sapian, Abdul Razak (Elsevier Ltd, 2017)
The void has been widely used in the multi-storey housing to induce natural ventilation in the living units for health and thermal comfort purposes. This research investigates the provision of the void to enhance natural ventilation performance in the living units of multi-storey housing. Malaysian affordable multi-storey housing (MAMSH), which is located in Malaysian suburban areas have been selected. The methods employed by the research are field measurement and computer simulation using CFD software. This study revealed that the indoor air velocity (m/s) in the living units of the studied building did not achieve the required rate for thermal comfort. However, by enlarging its size to 50% of the living units, natural ventilation performance in the living units is increased by up to 50.88%. The appropriate configuration of void been recommended based on the findings and venturi effect principle. This research contributes to the development of knowledge in enhancing natural ventilation performance in buildings. The suggestions might help the building industries to provide better designs option to enhance natural ventilation performance in the living units of multi-storey housing by providing an appropriate configuration of the void, and in turn, a sustainable living environment can be established.